PEMANFAATAN HASIL SAMPING PENGGILINGAN TEPUNG BERAS KETAN HITAM SEBAGAI BAHAN BAKU SNACK BARS DENGAN VARIASI TEPUNG LABU KUNING DAN JENIS GULA - AYUK FEBRIANA SHAHERTIAN PUTRI; YANNIE ASRIE WIDANTI; NANIK SUHARTATIK (Universitas Riau, 2017)
Black glutinous rice flour, by product from local cake industry, were potential for next processing. Pumpkinwas a local product that has a high nutritional value and rarely use as a food substance. The purpose of thisresearch was to increase the economic value of black glutinous rice flour by processing in to snack bars withincrement of pumpkin flour. The research carried out by using a full factorial randomized block designconsists of two factors. The first factor was the ratio of black glutinous rice flour and pumpkin flour, that is80:20, 70:30, and 50:50 meanwhile, second factors was kinds of sweetener, e.i: honey, palm sugar, andfructose. The research showed that the most satisfactory snack bars was the one that use 50% of blackglutinouse rice flour and 50% of pumpkin flour with honey as a sweeteners. With the product have characteristicas : 16,19% moisture content; 1.71% of ash; 6,77% of protein; 10.77% of fat; 24.32 of sugar; brown colour’s(2.78); soft (2.33); flavor of black glutinous rice flour (2.11); and flavor of pumpkin flour (2.67).